Penerapan Ground Theory, Middle Theory, dan Lower Theory dalam Proses Rekrutmen: Studi Literatur - Muhamad Sigid Safarudin (Sci-tech Journal, 2025)
This paper explores the application of Ground Theory, Middle Theory, and Lower Theory in recruitment processes. These theories represent different levels of abstraction in recruitment practices, ranging from strategic alignment to operational implementation. Ground Theory focuses on aligning recruitment with organizational goals, Middle Theory emphasizes structured practices, and Lower Theory deals with technical execution. This study uses a qualitative literature review method to analyze existing theories and their implications for recruitment. The findings suggest that integrating these three approaches can enhance the effectiveness of recruitment strategies.